Propensity for Clinically Meaningful Improvement and Surgical Failure After Anterior Cruciate Ligament Repair. Issue 4 (12th April 2023) - Batista, Jorge Pablo; Maestu, Rodrigo; Barbier, Jose; Chahla, Jorge; Kunze, Kyle N.
Background: Primary repair of the anterior cruciate ligament (ACL) confers an alternative to ACL reconstruction in appropriately selected patients. Purpose: To prospectively assess survivorship and to define the clinically meaningful outcomes after ACL repair. Study Design: Case series; Level of evidence, 4. Methods: Included were consecutive patients with Sherman grade 1-2 tears who underwent primary ACL repair with or without suture augmentation between 2017 and 2019. Patient-reported outcomes (Lysholm, Tegner, International Knee Documentation Committee, Western Ontario and McMaster Universities Osteoarthritis Index, and Knee injury and Osteoarthritis Outcome Score [KOOS] subscales) were collected preoperatively and at 6 months, 1 year, and 2 years postoperatively. The minimal clinically important difference (MCID) was calculated using a distribution-based method, whereas the Patient Acceptable Symptom State (PASS) and substantial clinical benefit (SCB) were calculated using an anchor-based method. Plain radiographs and magnetic resonance imaging (MRI) were obtained at 6 months, 1 year, and 2 years postoperatively. Results: A total of 120 patients were included. The overall failure rate was 11.3% at 2 years postoperatively. Changes in outcome scores required to achieve the MCID ranged between 5.1 and 14.3 at 6 months, 4.6 and 8.4 at 1 year, and 4.7 and 11.9 at 2 years postoperatively. Thresholds for PASS achievement ranged between 62.5 and 89 at 6 months, 75 and 89 at 1 year, and 78.6 and 93.2 at 2 years postoperatively. Threshold scores (absolute/change based) for achieving the SCB ranged between 82.8 and 96.4/17.7 and 40.1 at 6 months, between 94.7 and 100/23 and 45 at 1 year, and between 95.3 and 100/29.4 and 45 at 2 years. More patients achieved the MCID and PASS at 1 year compared with 6 months and 2 years. For SCB, this trend was also observed for non-KOOS outcomes, while for KOOS subdomains, more patients achieved the SCB at 2 years. High-intensity signal of the ACL repair (odds ratio [OR], 31.7 [95% CI, 1.5-73.4]; P = .030) and bone contusions on MRI (OR, 4.2 [95% CI, 1.7-25.2]; P = .041) at 1 year postoperatively were independently associated with increased risk of ACL repair failure. Conclusion: The rate of clinically meaningful outcome improvement was high early after ACL repair, with the greatest proportion of patients achieving the MCID, PASS, and SCB at 1 year postoperatively. Bone contusions involving the posterolateral tibia and lateral femoral condyle as well as high repair signal intensity at 1 year postoperatively were independent predictors of failure at 2 years postoperatively.